High-frequency fatigue after alpine slalom skiing - Tomazin, K.; Dolenec, A.; Strojnik, V. (European Journal of Applied Physiology, 2008)
The aim of the study was to examine the presence of high-frequency fatigue (HFF) after simulated alpine slalom skiing race. Eight male alpine skiers (18.4 ± 1.2 y.a., 182.3 ± 3.5 cm, 80.5 ± 3.4 kg) completed the study. Their average FIS points in slalom were 30.1 ± 5.4. After the special skiing warm up, the following initial tests were performed: blood lactate concentration, twitch response of the relaxed VL muscle, knee torque during low- (20 Hz) and high-frequency (100 Hz) electrical stimulation of vastus lateralis muscle, and maximum, voluntary isometric knee extension torque. Then, subjects performed slalom with 45 gates, whose duration was approximately 45 s. The same test sequence, except blood lactate test was used after slalom and the measurements started exactly 60 and 180 s after slalom. Blood lactate concentration measurement started exactly 3 and 5 min after slalom. A 1 × 3 repeated measures; time-series design was used with one within factor of time (before 60 s, and 180 s after skiing). The average blood lactate level increased from 1.6 (0.6) pre-slalom to 7.1(1.6) mmol-l 15 min post-slalom (F 2,14 = 70.1; P < 0.001). Sixty seconds after slalom, twitch contraction time shortened from 78.2 (5.7) pre-slalom to 66.0 (7.2) ms post-slalom (F 1.19,8.3 = 9.9; P < 0.05). Peak twitch torque was potentiated from 21.6 (3.8) to 26.4 (5.3) Nm (F 2,14 = 16.7; P < 0.05). Slalom reduced high-frequency torque from 64.4 (35) to 58.2 (34.2) Nm 60 s post-slalom (F 2,14 = 3.8; P < 0.05), while low-frequency torque stayed virtually the same. Slalom induced HFF, which is typical of SSC exercises of maximum intensity and short duration.